Smartphone security - Mamienko, Sergey; Mieshkov, V.I.; Zuyenok, I.І. (Видавництво НГУ, 2017)
According to eMarketer researchers, the total number of smartphones in active use on the planet exceeded the 2 billion unit in 2016 and amounted up to 2.16 billion against 1.9 billion in 2015 and 1.6 billion devices in 2014. A lot of owners of smartphones think that their communication, data exchange and privacy through their mobile or iPhones are completely protected from hacking and steeling as well as listening to, though they even can’t imagine that his or her phone has been hacked or their personal information has been sent to a cybercriminal. The main ways of possible hacking the information and tips how to provide safety of the information contained in smartphones are in the focus of this paper.
Keywords: Smartphone security; Безопасность смартфона